Deconstrucciones y críticas de las tecnologías occidentales de lo sensible - Cangi, Adrián (Nawi, 2021)
In order to understand the western technologies of the sensible we approach in this text a critical deconstruction, under an archaeological look at the discourses of "humanism" as an anthropology-technique of the colonial domain and a genealogical perspective of the problem of the "I" in the fields of "self-design” that concentrate the aesthetic-sensitive mode of the logistics of capital.